EVALUASI PENDIDIKAN DAN DAKWAH MUBALIGH PERSIS JAKARTA (STUDI DI PC PERSIS CIPAYUNG & PC PERSIS MATRAMAN) - Ihsan Abdul Haq (AT-TAWASUL, 2025)
Today's Persis preachers seem to be experiencing a "new trend" in their preaching activities, namely gaining as much sympathy as possible from the community. This is very different from the style of previous Persis preachers. They prioritize deep religious understanding. The development of the preacher education curriculum at the Branch level has not been well organized so that it is not yet adaptive to the problems of members and modern society, as well as the mentoring of preachers in training teaching and preaching methods is less innovative and creative. Likewise, the challenges of modern technology are still felt to be less than optimal. The preachers have not optimally utilized the digitalization of preaching, as evidenced by the fact that out of 80 preachers, only 3 people are active in preaching content. This study aims to analyze the evaluation of the development and mentoring of Persis preacher education at PC Persis Cipayung and PC Persis Matraman. This study uses a qualitative research method with an approach using case studies. The subjects of this study are. The data collection techniques used are observation, interviews and documentation. The data validity checking technique uses data triangulation techniques. Primary data sources were obtained directly by researchers from research objects in the field from the results of processing data from interviews with preachers, natural observations, and documents on Persis preaching education. While secondary data sources were obtained in the form of books, articles, journals, dissertation theses, and other documents. The results of this thesis research show. First, Educational Development requires curriculum updates that are more adaptive to technological developments and socio-cultural changes, as well as strengthening teacher capacity through ongoing training. Second, Preaching Assistance must be further improved through an innovative approach, to reach a wider audience, especially the younger generation who are more connected to the digital world. Third, the Evaluation of Development and Assistance in Education and Preaching shows the importance of updates in educational and preaching methods to strengthen Persis' influence in a society that continues to develop.